2002
DOI: 10.1364/josab.19.001401
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic second-harmonic generation of an antiferromagnetic film

Abstract: Second-harmonic generation of an antiferromagnetic film in Voigt geometry is calculated and analyzed. This calculation is carried out with an assumption of weak nonlinearity in a two-sublattice antiferromagnetic system. Second-harmonic waves are analyzed by the conventional approach of ordinary nonlinear optics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 8 publications
0
18
1
Order By: Relevance
“…It is because that a plane EMW of incidence can be decomposed into two waves, or a TE wave with the electric field normal to the incident plane and a TM wave with the magnetic field transverse to this plane. Due to no coupling between magnetic moments in the film and the TM wave (Lim, 2002(Lim, , 2006Wang & Li, 2005;Bai, et. al., 2007), the incident TM wave does not excite the linear and SH magnetizations, so can be ignored.…”
Section: Second Harmonic Generation In Antiferromagnetic Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is because that a plane EMW of incidence can be decomposed into two waves, or a TE wave with the electric field normal to the incident plane and a TM wave with the magnetic field transverse to this plane. Due to no coupling between magnetic moments in the film and the TM wave (Lim, 2002(Lim, , 2006Wang & Li, 2005;Bai, et. al., 2007), the incident TM wave does not excite the linear and SH magnetizations, so can be ignored.…”
Section: Second Harmonic Generation In Antiferromagnetic Filmsmentioning
confidence: 99%
“…Many investigations have been carried out on nonlinear guided and surface waves (Wang & Awai,1998;Almeida & Mills, 1987;Kahn, et. al., 1988;Wright & Stegeman, 1992;Boardman & Egan,1986), second-harmonic generation (Lim, 2002(Lim, , 2006Fiebig et. al, 1994Fiebig et.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the study is focused on the generation of second harmonic waves from antiferromagnetic/dielectric multilayers induced by incident intense far infrared electromagnetic field. This is an extension of the previous calculation on the generation of second harmonic waves from a simple uniaxial two-sublattice antiferromagnetic film (FeF 2 ) with weak nonlinearity [13,14], within the conventional methods of nonlinear optics [15,16]. In this paper, the approach being used in the analysis of linear and second harmonic transmission and reflection of antiferromagnetic/dielectric (FeF 2 /ZnF 2 ) multilayers is entirely based on conventional nonlinear optics and the transfer matrix technique [1,14].…”
Section: Introductionmentioning
confidence: 56%
“…It should be noted that nonlinear magnetic materials such as FeF2 and MnF2 exhibit interesting properties that can enhance the performance of THz devices [27][28][29][30][31]. To the authors' knowledge, no published work has been reported on the analytical study of nonlinear multilayer graphene-based structures with nonlinear magnetic materials.…”
Section: Introductionmentioning
confidence: 99%